'Hobson's choice': a qualitative study of consent in acute surgery. Issue 10 (8th October 2020) - Howard, Anthony; Webster, Jonathan; Quinton, Naomi; Giannoudis, Peter V
Abstract : Objectives: The study aimed to understand through qualitative research what patients considered material in their decision to consent to an acute surgical intervention. Participants, setting and intervention: The patients selected aged between 18 and 90, having been admitted to a major trauma centre to undergo an acute surgical intervention within 14 days of injury, where English was their first language. Data saturation point was reached after 21 patients had been recruited. Data collection and analysis were conducted simultaneously, through interviews undertaken immediately prior to surgery. The data were coded using NVIVO V.12 software. Results: The key theme that originated from the data analysis was patients were unable to identify any individual risk that would modify their decision-making process around giving consent. The patient's previous experience and the experience of others around them were a further theme. Patients sensed that there were no non-operative options for their injuries. Conclusion: This is the first study investigating what patient considered a material risk in the consent process. Patients in this study did attribute significance to past experiences of friends and family as material, prompting us to suggest that the surgeon asks about these experiences as part of the consent process. Concern about functional recovery was important to patients but insufficient to stop them from consenting to surgery, thus could not be classified as material risk.